A Nondestructive, Reproducible Method of Measuring Joint Reaction Force at the Distal Radioulnar Joint - Canham, Colin D. (J Hand Surg Am, 2015)
PURPOSE: To develop a nondestructive method of measuring distal radioulnar joint (DRUJ) joint reaction force (JRF) that preserves all periarticular soft tissues and more accurately reflects in vivo conditions. METHODS: Eight fresh-frozen human cadaveric limbs were obtained. A threaded Steinmann pin was placed in the middle of the lateral side of the distal radius transverse to the DRUJ. A second pin was placed into the middle of the medial side of the distal ulna colinear to the distal radial pin. Specimens were mounted onto a tensile testing machine using a custom fixture. A uniaxial distracting force was applied across the DRUJ while force and displacement were simultaneously measured. Force-displacement curves were generated and a best-fit polynomial was solved to determine JRF. RESULTS: All force-displacement curves demonstrated an initial high slope where relatively large forces were required to distract the joint. This ended with an inflection point followed by a linear area with a low slope, where small increases in force generated larger amounts of distraction. Each sample was measured 3 times and there was high reproducibility between repeated measurements. The average baseline DRUJ JRF was 7.5 N (n = 8). CONCLUSIONS: This study describes a reproducible method of measuring DRUJ reaction forces that preserves all periarticular stabilizing structures. This technique of JRF measurement may also be suited for applications in the small joints of the wrist and hand. CLINICAL RELEVANCE: Changes in JRF can alter native joint mechanics and lead to pathology. Reliable methods of measuring these forces are important for determining how pathology and surgical interventions affect joint biomechanics.